Mycorrhizae in sedges as related to root character and its ecological significance - T., Muthukumar; K., Udaiyan; K., Vasantha; D., Kleiner; S., Manian (Universiti Putra Malaysia Press, 1999)
Twenty four sedges were examined to assess the role of root characters on mycorrhizal status. Vesicular-arbuscular mycorrhizal (VAM) injection was positively related to root thickness and negatively to root hair number and length. Dried mycorrhizal roots of Bulbostylis barbata, Cyperus cyperinus. C. kyllingia and Fimbristylis ovata served as inocula oj VAMJungi in pot culture study indicating that mycorrhizal sedge roots could act as inocula in initiating and reviving mycorrhizae in natural soils.